In situ neutron diffraction of NaAlD4/carbon black composites during decomposition/deuteration cycles and the effect of carbon on phase segregation. (19th September 2022) - Palm, Rasmus; Tuul, Kenneth; Elson, Frank; Nocerino, Elisabetta; Forslund, Ola K.; Hansen, Thomas C.; Aruväli, Jaan; Månsson, Martin
Abstract: The influence on the decomposition and reforming of the hydrogen storage material NaAlH4 by adding relatively low amounts of mesoporous carbon black is investigated with in situ diffraction. A 60:40 NaAlH4 /carbon black composite is prepared via ball milling and characterised ex situ via X-ray diffraction, gas adsorption, temperature-programmed decomposition, and dehydrogenation/hydrogenation cycling methods. The prepared composite is deuterated, and the crystalline phase composition is determined with in situ neutron powder diffraction method during multiple decomposition/deuteration cycles. Changes in the crystalline phase composition start slightly below the melting temperature of the pristine alanate, whereas the release of deuterium starts at considerably lower temperatures. The decomposition of Na3 AlD6 to NaD is almost completely reversible at the applied low deuterium pressures of ≥2 MPa. Thus, the strong effect of even low concentrations of a mesoporous carbon black on the capability to store H2 reversibly is showcased and analysed in-depth. Graphical abstract: Image 1 Highlights: NaAlD4 confined in a mesoporous carbon black. In situ neutron powder diffraction during dedeuteration/deuteration cycles. Crystalline composition determination at all experimental instances. D2 release at highly lowered temperatures from small-particulate/amorphous phase. Full regeneration of Na3 AlD6 from NaD at low deuterium pressures (≤20 bar).